2002
DOI: 10.1088/0022-3727/35/12/311
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic study of a supersonic plasma jet generated by an ICP torch with a convergent-divergent nozzle

Abstract: A supersonic argon and argon-hydrogen (3-5{%}) plasma jet generated by an induction plasma torch is studied by means of the methods of optical emission spectroscopy. The torch was operated at the input power of 20 kW and near atmospheric pressure. The supersonic jet with a periodic structure of expansion and compression zones is created by expanding the plasma through the Laval nozzle into a chamber maintained at the pressure around 1.8 kPa. Atomic argon lines with the upper level energies ranging from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…An overpressure minimum at the axial position of 48.6 mm is accompanied by the Mach number, axial velocity maxima, and a slight temperature minimum. This detects a beginning of compression and expansion waves generation reported in papers dealing with supersonic plasma jets; see for example, [44]- [46].…”
Section: Results Of Calculationmentioning
confidence: 62%
“…An overpressure minimum at the axial position of 48.6 mm is accompanied by the Mach number, axial velocity maxima, and a slight temperature minimum. This detects a beginning of compression and expansion waves generation reported in papers dealing with supersonic plasma jets; see for example, [44]- [46].…”
Section: Results Of Calculationmentioning
confidence: 62%
“…The relationship between T exc and T e has been investigated over the past few decades, and the resulting studies reported the comparisons performed in microwave discharge [2,3,9], plasma jet [10], or theoretically [11] at atmospheric pressure. However, few studies have been attempted in high electron density at low pressure plasmas such as industrial processing plasmas in which various plasma sources are needed for advanced technology.…”
Section: Introductionmentioning
confidence: 99%
“…For the estimation of electron density, the measured H b line profile was compared with a calculated one. Since the lines H b profile is broadened mainly due to Stark effect and the effect depends on electron density, this method has often been employed for the estimation of electron density when plasma contains hydrogen [19,20]. We employed the tables [21] to obtain the theoretical one.…”
Section: Introductionmentioning
confidence: 99%